Batuan dan mineral / Dan Green; Penerjemah, Kandi Sekarwulan; Editor, Rian Irawan dan Winny Rachmayanti - GREEN, Dan; KANDI Sekarwulan; RIAN Irawan; WINNY Rachmayanti (Erlangga, 2013)
128 hlm. : Ilus. ; 22 cm.